BACK MASSAGE PADA KUALITAS TIDUR IBU HAMIL TRIMESTER III - Yuli Yantina; Nita Evrianasari (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2020)
ABSTRACT Background: During pregnancy, pregnant women will experience a variety of changes in reproduction that are physiological and sometimes pathological. Sleep difficulties are generally more common in early pregnancy. Then this sleepless complaint will reappear at the end of pregnancy. Persistent sleep disorders will interfere with the physical and psychological pregnant women. Purpose of this study is to know the effect of back massage on sleep quality of trimester III pregnant women Methods: Research type experimental research, design pre experiment designs with one group pretest posttest design. Population in this research is trimester mother III at BPM Tiara Iswantika Wonosari District of Pekalongan Regency of East Lampung year 2018, sample taken counted 29 people with purposive sampling technique. Analysis in this research use paired sample t test.Results of statistical tests showed that the mean maternal sleep quality score on the measurement result using the Pittsburgh Sleep Quality Index (PSQI) questionnaire before (pretest) the back massage intervention was 6,28±1,461 and after (posttest) the back massage intervention was 5, 03±1,349 with an mean difference of 1,241±0,739. In result of paired sample t test showed back massage proved to have an effect on to sleep quality of pregnant woman trimester III (p-value 0,000 <a0,05). Conclusion: With the results of this study is expected pregnant women can do back massage therapy to reduce tension, relax the body and improve sleep quality.Suggestion Currently there is still no counseling related to back massage, so health workers should be able to provide back massage counseling to pregnant women because back massage has become part of supporting therapy in the health sector to improve health status, especially in improving the quality of sleep for pregnant women. Keywords : Sleep quality, back massage ABSTRAK Latar Belakang: Pada masa kehamilan, ibu hamil akan mengalami berbagai perubahan pada sistrem reproduksi yang bersifat fisiologis dan terkadang bersifat patologis. Kesulitan tidur umumnya lebih banyak dialami pada awal kehamilan. Kemudian keluhan sulit tidur ini akan kembali muncul pada akhir kehamilan. Gangguan tidur yang terus menerus akan mengganggu fisik dan kejiwaan ibu hamil.Tujuan: diketahuinya pengaruh back massage terhadap kualitas tidur ibu hamil trimester III Metodologi: Jenis penelitian experimental research, desain pre experiment designs dengan rancangan one group pretest posttest. Populasi dalam penelitian ini adalah ibu trimester III di BPM Tiara Iswantika Wonosari Kec. Pekalongan Kab. Lampung Timur tahun 2018, sampel yang diambil sebanyak 29 orang dengan teknik purposive sampling. Analisis dalam penelitian ini menggunakan uji paired sample t test.Hasil: uji statistik menunjukkan bahwa Rata-rata skor kualitas tidur ibu hamil pada hasil pengukuran menggunakan kuesioner the Pittsburgh Sleep Quality Index (PSQI) sebelum (pretest) intervensi back massage adalah 6,28±1,461 dan setelah (posttest) intervensi back massage adalah 5,03±1,349 dengan selisih rata-rata 1,241±0,739. Pada hasil uji paired sample t test menunjukkan back massage terbukti berpengaruh terhadap kualitas tidur ibu hamil trimester III (p-value 0,000<a0,05). Kesimpulan: Dengan hasil penelitian ini diharapkan ibu hamil dapat melakukan terapi back massage untuk menurunkan ketegangan, merileksasi tubuh dan meningkatkan kualitas tidur.Saran Saat ini masih belum ada penyuluhan terkait back massage maka hendaknya bagi tenaga kesehatan dapat memberikan penyuluhan back massage kepada ibu hamil karena back massage telah menjadi bagian dari terapi penunjang dalam bidang kesehatan untuk meningkatkan derajat kesehatan terutama dalam meningkatkan kualitas tidur ibu hamil. Kata Kunci : Kualitas tidur, back massage